ANALISIS KELAYAKAN FINANSIAL LADA PUTIH Di KABUPATEN BANGKA - NURASA, TJETJEP (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006, 2012)
This study was implemented in 2002 in Bangka Regency as central production of muntok pepper, was chosen as a research location. The objectives of study were: ( i)to analyze the financial visibility of pepper farm, (ii)to identify the channel of white pepper marketing and its margin in each agent of marketing, and ( iii)to analyze the comparative and competitive advantages of white pepper. Research used the method of structured survey. Primary data were collected from 60 farmers, 15 merchants, 5 agents of processing, and exporters. While secondary data were collected from Central Agency of Statistics, the Office of Estate Crops, and Institutions of Research related to this study. The financial visibility of pepper farm was counted by using method of input-output analysis to get value of Beneficial Cost Ratio (B/C Ratio), Net Present Value ( NPV), and Internal Rate Of Return (IRR). While the value of comparative and competitive advantages were estimated by using method of Policy Analysis Matrix ( PAM). Results showed that, period of pepper farm was 7 years where in the fourth year, pepper crop started create production of Rp.15.116 million and earnings of Rp.9.4. In fourth year, it gave the highest production and earnings, namely Rp.21.511 million and Rp.12.9 million, respectively. While in the seventh year, it reached the lower production of Rp.8.960 million and earnings of Rp.5.620 million/ha/year. At interest rate of 24 percent, it took NPV of Rp.4.12 million per hectare with B/C Ratio of 1.23. At level of input-output actual, break-even point of pepper farm reached IRR of 32,49 percent. Eighty percent of farmers sold their white pepper to small collecting merchant and the others (70%) sold to large collecting merchant. The small collecting merchant (80%) sold white pepper to large collecting merchant and then large collecting merchant sold them to large merchant/exporter. The highest profit margin successively happened at large collecting merchant (Rp.680), large merchant/ exporter (Rp.1.600), and small collecting merchant (Rp.565)/kg pepper seed. The highest value of DRCR was happened in the fourth year, namely 0.18. While in three and sixth year, it reached DRCR of 0.25 and 0.34, respectively. At the other side, the value of competitive advantage also saw adequately, that was 0.36 (in three year), 0.38 ( in fourth year), and 0.26 ( in sixth year).
Keywords: White Pepper; Financial Feasibily,